Advances in the clinical management of pediatric kidney transplantation - Saatçi, Ümit (The Turkish Journal of Pediatrics, 1996)
Renal transplantation is the best form of renal replacement therapy for children reaching end-stage renal failure. The first human transplantation was performed by Dr. Voronoy from a cadaver donor in 1933; however, because of the lack of immunological laboratory assessments, this transplantation resulted in rejection. Progress in immunological evaluation and new immunosuppressive drugs have improved survival in renal transplantation. The first renal transplantation in Turkey was performed by Dr. Haberal et al. on November 3, 1975. This child was one of five siblings with juvenile nephronophytisis, and the mother was the donor. Dr. Haberal has thus pioneered renal transplantation in Turkey. In the following years Dr. Haberal initiated cadavral transplantation in our country in collaboration with Eurotransplant. He has also contributed to the law concerning transplantation in Turkey. Subsequently many transplantation centers have been developed in the country. In spite of marked progress in transplantation technology, pediatric transplantation has not improved as fast as adult transplantation. This is due to several factors, such as the difference in the etiological factors leading to chronic renal failure, technical factors, growth and sexual development, factors relevant to infections and vaccinations, and psychological problems.